PENGARUH DISIPLIN KERJA, MOTIVASI KERJA, KOMITMEN ORGANISASIONAL, DAN KEPUASAN KERJA TERHADAP KINERJA GURU MTs SE-KECAMATAN KEDUNGWUNI PEKALONGAN - Nur Malaq Mahmudah, 12.5202.0115 (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to analyze the influence of Influence Work Discipline, Work Motivation, Organizational Commitment and Job Satisfactionon to Teacher Performance in MTs Ministry of Religius at Kedungwuni District of Pekalongan.In this study population of all primary school teachers in MTs Ministry of Religius at Kedungwuni District of Pekalongan Â civil servants, while the samples used as many as 141 people as respondents to the census technique. With a respondent criteria PNS Elementary Teacher in MTs Ministry of Religius at Kedungwuni District of Pekalongan. the District Education Office.Measure mentsusing 5 Likert scale ( five ) alternative answers.Test instrumentsused are validity and reliability. While the test model used is the coefficient of determinationand F test ( goodnes of Fit ). Test this hypothesisusing regression analysis.Based on the results of the study can be summarized asfollows: (i) Discipline positive and significant impact on teacher performance, (ii) MotivationÂ positive and significant impact on teacher performance, (iii) Organizational Commitment positive and significant impact on teacher performance and (iv) Job Satisfaction has negative effect against Teacherâs Performance. Keywords : Discipline of Work, Work Motivation, Organizational Commitment, Job Satisfaction and Teacherâs Performance.